Mining event structures from web videos - WU, Xiao (Institutional Knowledge at Singapore Management University, 2011)
The article is discussing the issues of mining event structures from Web video search results using text analysis, burst detection, and clustering as with the proliferation of social media, the volume of Web videos have grown exponentially.